Penerapan Metode Inquiri pada Pembelajaran Matematika untuk Meningkatkan Aktivitas dan Prestasi Belajar Siswa Kelas VI Semester I SD Integral Al Amiin Hidayatullah Timika Tahun Pelajaran 2021/2022 - Ramlah Ramlah (LPPM Politeknik Pratama, 2024)
In mathematics learning in class VI of Al Amiin Hidayatullah Timika Integral Elementary School, there are still many students who experience difficulties in understanding the concepts being taught. The aim of this research is to increase the activity and learning achievement of class VI students in the first semester of Al Amiin Integral Elementary School. This research uses quantitative and qualitative approaches. From the results of the research conducted, it was concluded that the application of the inquiry method was successful in achieving the objectives of this research.